Sessile Serrated Lesions: Searching for the True Prevalence and Risk Factors in China - Yao, Bing-Yue; Zhang, Li; Wu, Chuan-Xia; Zheng, Liang; Duan, Ben-Song; Xu, Qin-Wei; Lian, Jing-Jing; Zhang, Hai-Bin; Wang, Yu; Cao, Jia (Turkish Journal of Gastroenterology, 2025)
Background/Aims: Growing recognition identifies sessile serrated lesions (SSL) as colorectal cancer (CRC) precursors. However, the SSL detection rate remains debatable and lacks a definitive consensus. Additionally, understanding the influencing factors in SSL development is limited. We aim to retrospectively analyze the true prevalence and risk factors of SSL in China. Materials and Methods: This retrospective study collected medical data from patients who underwent colonoscopy at the Endoscopy Center of Shanghai East Hospital affiliated with Tongji University between March 1, 2019 and February 28, 2022. Data were sourced through the electronic medical record system and included information such as age, sex, lesion location, number, and pathology. This study predominantly focused on the detection rate and the clinical and endoscopic features of SSL. Results: Of 72 287 colonoscopies in 3 years, 3905 cases were histologically confirmed as SSL. Among them, 2290 (58.6%) were male, and 1615 (41.4%) were female. The overall SSL detection rate was 5.40%, slightly surpassing Asian/Chinese averages but lower than Western rates. Males had a higher SSL detection rate (6.1%) than females (4.6%). Univariate analysis revealed a significant association between SSL with dysplasia/adenocarcinoma (SSL-D/AD) and obesity (Body Mass Index, BMI ≥ 24), CRC family history, and hypertension. After multivariable logistic regression, only obesity (BMI ≥ 24) remained a statistically significant independent risk factor for SSL-D/AD. Conclusions: The SSL detection rate at our center is 5.4% and increases with age. Males have a significantly higher detection rate than females. Our findings suggest that endoscopists should consider risk factors for SSL-D/AD, such as obesity, CRC family history, and hypertension. Cite this article as: Yao B-Y, Zhang L, Wu C-X, et al. Sessile serrated lesions: Searching for the true prevalence and risk factors in china. Turk J Gastroenterol. 2025;36(1):15-23.